210 - Are visits allowed? The impact of the COVID-19 pandemic on care home visitation and care delivery in the UK. (October 2021) - Giebel, Clarissa; Hanna, Kerry; Cannon, Jacqueline; Tetlow, Hilary; Marlow, Paul; Shenton, Justine; Mason, Stephen; Rajagopal, Manoj; Gabbay, Mark
Abstract : Background: COVID-19 has caused the sudden closure of care homes to the outside world, to stem the virus from infecting some of the most vulnerable groups of people – older adults residing in care homes. With very little knowledge to date, we aimed to explore the impact of COVID-19 on care provision and visits in care homes from staff and family members' perspectives. Methods: Care home staff and family carers of people living with dementia (PLWD) across the UK were recruited via convenience sampling and participated via telephone or Zoom. Participants took part in a semi-structured remote interview. Baseline data were collected between October and November 2020, and follow-up interviews were collected throughout March 2021. Anonymised transcripts were analysed separately by two research team members using thematic analysis, with codes discussed and themes generated jointly, supported by research team input. Results: 42 participants (26 family carers and 16 care home staff) took part in the baseline interviews, and 20 purposefully sampled participants (11 family carers and 9 care home staff) were followed up. Prior to vaccination roll out in the UK, at baseline, family carers expressed concern about a lack of clear guidance throughout the pandemic, with care homes delivering care differently and disparities noted in the levels and types of visiting allowed for family members. Lack of communication between care homes and family members, but also government and care homes, led to family carers feeling excluded and concerned about the well-being of their relative. Data on follow-up interviews are still being analysed. Conclusions: This is the first empirical evidence to show how the pandemic has caused severe difficulties in providing adequate care for care home residents, with not only residents, but also care home staff and family carers being negatively affected. Follow-up data will shed light onto the impact of vaccination and eased visitation rights put in place since March 2021 on care delivery and connections between family carers and residents.